Implementasi Pemberian Remisi Sakit Berkepanjangan Berdasarkan Undang-Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan (Studi Kasus Rumah Tahanan Kelas I Pondok Bambu) - Simanjuntak, Johannes; Sulastri, Lusia (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Humanitarian remission is granted based on humanitarian considerations as stipulated in Article 29 of Regulation of the Minister of Law and Human Rights Number 16 of 2023. This remission is granted to prisoners who have been sentenced to a maximum of 1 (one) year, are over 70 (seventy) years of age, and/or suffer from a chronic illness. Prolonged illness remission is granted on Health Day, which is April 7, to prisoners who have served a minimum of 6 (six) months, have good behavior, are not listed in the F register, and meet the provisions of Article 34C of Government Regulation Number 99 of 2012. The amount of remission granted ranges from 1 (one) to 6 (six) months. This study aims to analyze the implementation of Long-Term Illness Remission based on Law No. 22 of 2022 concerning Corrections at the Pondok Bambu Class I Detention Center and to identify the obstacles encountered. The results of the study show that the implementation of remission has been in accordance with applicable legal provisions through the application procedure, medical examination, and approval by the authorities. The data shows that during 2023–2025, there were three prisoners who received long-term sick remission. The obstacles found include administrative and institutional factors, as well as limitations in facilities and infrastructure, so improvements are needed to make the implementation of remission more effective and efficient.